Effect of a U:G mispair on the water around DNA - Mardt, Andreas; Gorriz, Rene F.; Ferraro, Federica; Ulrich, Philip; Zahran, Mai; Imhof, Petra (Biophysical Chemistry, 2022)
DNA repair proteins are able to discriminate DNA lesions among an abundance of intact DNA with high selectivity. To investigate detectable characteristics of one specific lesion, we compare statistical results from molecular dynamics simulations of two different DNA in water, one with an intact C:G pair and one that contains a U:G mispair, and perform a comparative analysis of the water dynamics around the two. Our data show that in addition to the local DNA conformation, also the surrounding water shell exhibits significant differences that may help mispair discrimination. The chemical groups which account for a U:G mispair to exhibit a wobble conformation instead of the ‘proper’ Watson-Crick pairing of a C:G pair, that is an oxygen atom (in uracil) instead of an amino group (in cytosine), also order the water molecules around the bases such that they act predominantly as hydrogen-bond donor or acceptor to the uracil or cytosine base, respectively. These changes in water conformation stretch into the second solvation shell, which may be exploited by repair enzymes to achieve lesion detection with high efficiency.
CRIS-Team Scopus Importer:2022-03-18

Effect of the Hydration Shell on the Carbonyl Vibration in the Ala-Leu-Ala-Leu Peptide - Hassan, Irtaza; Ferraro, Federica; Imhof, Petra (Molecules, 2021)
The vibrational spectrum of the Ala-Leu-Ala-Leu peptide in solution, computed from first-principles simulations, shows a prominent band in the amide I region that is assigned to stretching of carbonyl groups. Close inspection reveals combined but slightly different contributions by the three carbonyl groups of the peptide. The shift in their exact vibrational signature is in agreement with the different probabilities of these groups to form hydrogen bonds with the solvent. The central carbonyl group has a hydrogen bond probability intermediate to the other two groups due to interchanges between different hydrogen-bonded states. Analysis of the interaction energies of individual water molecules with that group shows that shifts in its frequency are directly related to the interactions with the water molecules in the first hydration shell. The interaction strength is well correlated with the hydrogen bond distance and hydrogen bond angle, though there is no perfect match, allowing geometrical criteria for hydrogen bonds to be used as long as the sampling is sufficient to consider averages. The hydrogen bond state of a carbonyl group can therefore serve as an indicator of the solvent's effect on the vibrational frequency.
CRIS-Team WoS Importer:2021-05-14

Study of the Wilcox torsion balance in solution for a Troger's base derivative with hexyl-and heptyl substituents using a combined molecular mechanics and quantum chemistry approach - Heßelmann, Andreas; Ferraro, Federica (Journal of Molecular Modeling, 2019)
The folding equilibrium of the Wilcox torsion balance in solution has been studied using a molecular mechanics method for sampling the conformational space and semi-empirical and density-functional quantum chemistry methods for characterizing the relative stabilities of various solute-solvent clusters extracted with the aid of the MD-quench technique from the different simulations that were performed. The role of the solvent environment has been analyzed by choosing four solvents of different polarities, namely water, acetone, tetrachloromethane, and n-hexane. In all cases, it is found that the attractive intramolecular interactions in folded conformations are strongly compensated by the increase of the solute-solvent interaction energies when the molecule unfolds. The latter can be well explained by the larger number of solvent molecules that can bind to the Wilcox molecule when in an unfolded conformation. The results of this work therefore support the experimental results of Yang et al. (Nature Chem 5:1006, 2013) that the folding free energy of the Wilcox balance is strongly reduced in solution as compared to the gas phase.
CRIS-Team WoS Importer:2019-03-06